Lustration in Ukraine: politico- legislative analysis - Денисюк, С. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article concerns the historical origin of lustration processes, the nature of lustration and its basic types (public, economic and political). Lustration is analyzed from political and legal point of view, the requirements for persons considered to be checked are scrutinized. The author distinguishes problematic points of lustration processes that can be used to deal with political rivals. Attention is focused on the need to accelerate the implementation of lustration based on objective indicators and making purge of government officials. The author suggests making a number of amendments to the law on lustration to increase its effectiveness.